The Influence of Discipline and Boredom on the Memorization Ability of Quranic Verses among Students in the Tahfidz Program at MTs Muammar Gandi, Sidrap Regency - Trisnawati Trisnawati; Muzakkir Muzakkir; St. Aminah; Sitti Jamilah Amin; Buhaerah Buhaerah (The Future of Education Journal, 2025)
This study is motivated by the limited empirical research that simultaneously examines the influence of discipline and learning fatigue on the Quran memorization ability at the Madrasah Tsanawiyah level in Indonesia. The study aims to (1) analyze the effect of discipline, (2) test the effect of learning fatigue, and (3) measure the combined effect of both on the Quran memorization ability of students in the Tahfidz program at MTs Muammar Gandi, Sidenreng Rappang Regency, academic year 2025/2026. The research uses a quantitative approach with an ex post facto correlational-regression design. A population of 39 students was taken entirely through total sampling; after data cleaning, 34 students remained. Data were collected through a Likert scale questionnaire, non-participant observation, and documentation, then analyzed using descriptive statistics and multiple linear regression with SPSS 26. The results show that discipline has a significant positive effect partially (t = 3.444; Sig. = 0.002), learning fatigue has no significant partial effect (t = -1.397; Sig. = 0.172), but both simultaneously have a significant effect (F = 10.890; Sig. = 0.000) with a contribution of 28.7%. These findings support Skinner's behaviorism theory and Ebbinghaus's forgetting curve, which suggest that Quran memorization is more determined by discipline than temporary fatigue. The study concludes that discipline is the main factor in the success of Tahfidz programs. Practical implications: Madrasah and pesantren managers need to strengthen the discipline system of muroja’ah and early detection of fatigue.